2021
DOI: 10.1155/2021/6675176
|View full text |Cite
|
Sign up to set email alerts
|

Model Testing of Encased Stone Column Composite Foundations under Traffic Loads

Abstract: In soft soil foundations, geogrid encased stone column composite foundation technology has been widely applied and developed in recent years due to its efficient treatment. In this study, eight groups of laboratory model tests were performed in a large-scale testing tank to investigate the bearing mechanism and stress characteristics of the composite foundation of geogrid encased stone columns under traffic loads with different cyclic load ratios. The stress at the bottom of the stone column and settlement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Li Tianbao et al [12] carried out an indoor model test of a rigid-flexible, pile-bearing, reinforced bedding composite foundation and compared and analysed the bearing properties of a rigid-flexible pile and flexible pile-bearing reinforced bedding composite foundation under cyclic loading. Yuan et al [13] carried out an indoor model test of a reinforced gravel pile composite foundation under multiple sets of traffic loads and analysed the effect of the cyclic loading ratio on the bearing properties of a reinforced gravel pile composite foundation. Zhu et al [14,15] investigated the bearing characteristics of a pile-soil composite foundation under long-term cyclic loading by indoor dynamic modelling tests.…”
Section: Introductionmentioning
confidence: 99%
“…Li Tianbao et al [12] carried out an indoor model test of a rigid-flexible, pile-bearing, reinforced bedding composite foundation and compared and analysed the bearing properties of a rigid-flexible pile and flexible pile-bearing reinforced bedding composite foundation under cyclic loading. Yuan et al [13] carried out an indoor model test of a reinforced gravel pile composite foundation under multiple sets of traffic loads and analysed the effect of the cyclic loading ratio on the bearing properties of a reinforced gravel pile composite foundation. Zhu et al [14,15] investigated the bearing characteristics of a pile-soil composite foundation under long-term cyclic loading by indoor dynamic modelling tests.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, alternative methods that do not involve massive excavation but can reinforce the soil in place have come to be preferred. Among them, the use of stone columns has gained attention in the geotechnical community [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Various researchers [20][21][22] analyzed the behavior of stone columns in the soft soil using the finite-element method and investigated the role of various parameters, such as the depth ratio, the column diameter and stiffness, and the soil's friction angle and Poisson's ratio. A study [8] concluded that the stiffness of the stone column material is a critical parameter controlling the settlement of the treated soil, observing that stiffer columns are associated with smaller vertical and lateral displacements. Finally, it was also pointed out [23] that stone columns can be used to reduce the liquefaction potential.…”
Section: Introductionmentioning
confidence: 99%